Tumorigenesis in the multiple intestinal neoplasia mouse: Redundancy of negative regulators and specificity of modifiers - Halberg, Richard B. (The National Academy of Sciences, 2000)
The interaction between mutations in the tumor-suppressor genes Apc and p53 was studied in congenic mouse strains to minimize the influence of polymorphic modifiers. The multiplicity and invasiveness of intestinal adenomas of Apc(Min/+) (Min) mice was enhanced by deficiency for p53. In addition, the occurrence of desmoid fibromas was strongly enhanced by p53 deficiency. The genetic modifier Mom1 and the pharmacological agents piroxicam and difluoromethylornithine each reduced intestinal adenoma multiplicity in the absence of p53 function. Mom1 showed no influence on the development of desmoid fibromas, whereas the combination of piroxicam and difluoromethylornithine exerted a moderate effect. The ensemble of tumor suppressors and modifiers of a neoplastic process can be usefully analyzed in respect to tissue specificity and synergy.